2018
DOI: 10.1007/s12020-018-1719-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal low-protein diet during lactation combined with early overfeeding impair male offspring’s long-term glucose homeostasis

Abstract: The combination of low-protein diet in breastfeeding dams with postnatal overfeeding disturbed the offspring's glucose metabolism in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The composition of the microbiota after birth is mainly influenced by dietary and environmental factors. Maternal obesity [36], antibiotic use [37,38], and breast-feeding/formula feeding have been associated with modifications of microbiota composition [39]. As with the results of this study, low-protein diets significantly altered piglet gut microbiota.…”
Section: Discussionsupporting
confidence: 74%
“…The composition of the microbiota after birth is mainly influenced by dietary and environmental factors. Maternal obesity [36], antibiotic use [37,38], and breast-feeding/formula feeding have been associated with modifications of microbiota composition [39]. As with the results of this study, low-protein diets significantly altered piglet gut microbiota.…”
Section: Discussionsupporting
confidence: 74%
“…17 The low-protein chow was prepared at the Laboratory of Cellular Biology at State University of Maringa, Brazil (constituents described in Table 1), as previously described. 15,18 The experimental analysis was carried out at PND 120 (Fig. 1).…”
Section: Animals and Dietary Protocolmentioning
confidence: 99%
“…Several animal and epidemiological studies indicated the importance of prenatal diet on the developmental origin of health and diseases. Especially, an adequate amount of prenatal protein is crucial in the metabolic health of the adult offspring [20][21][22][23][24] . Fetal organs' growth and metabolism depend on maternal nutrition and a maternal LP diet impacts several fetal organs at the expense of some organs such as the brain.…”
Section: Introductionmentioning
confidence: 99%